Primer pairs specificity test for frog meat identification using PCR technique - Haryono, Norman Yoshi; Khusufi, Rizqi Layli; Pangesti, Delia Wahyu; Susanti, Evi; Mariana, Rina Rifqie; Wardani, Hartati Eko; Salim, Norazlinaliza (Universitas Gadjah Mada, Indonesia, 2023)
Halal food assurance is becoming more important with the growth of the halal industry globally. Adulteration of halal meat products using non-halal sources such as pork, dog, boar, and even frog meat has become a major problem for moslems. The purpose of this study is to initiate the method for frog meat identification using polymerase chain reaction (PCR) technique. In this study, three primer pairs (Fk1-Rk1, Fk2-Rk2, Fk3-Rk3) were analyzed for their specificity toward frog meat against other common halal meat sources such as beef, chicken, shrimp, squid, and mackerel. The visualization of DNA amplification showed that primer pair Fk1-Rk1 produced primer-dimer, thus cannot be used for this circumstance. Primer pair Fk2-Rk2 showed a better result where DNA amplicon was produced at ~100 bp for frog meat and no amplicons for other meat. Primer pair Fk3-Rk3 showed a different pattern of DNA amplification for all the meat tested, where the amplicon of frog meat was shown at ~100 bp, while the other meat showed multiple amplicons or none. In conclusion, primer pairs Fk2-Rk2 and Fk3-Rk3 showed their potential as primer pairs for frog meat identification using PCR for implementing halal food assurance, although sensitivity analysis needs to be investigated.